"Nothing is sweet in my mouth": Food, identity, and religion in African Lisbon. Issue 3 (1st October 2016) - Johnson, Michelle C.
ABSTRACT: Here I explore food and eating and their connection to identity and religion among immigrants and refugees from Guinea-Bissau living in and around Lisbon, Portugal. I first demonstrate the importance of food to fieldwork in transnational settings, as well as to the understanding of the experience of migration. I show how different foods and eating styles mark boundaries and distinctions between homeland and host country, Africans and Europeans, and Muslim and "Christian" (non-Muslim) Guineans, and allow people to play with these boundaries while making powerful statements about identity and religion in African Lisbon. I argue that during the War of June 7th, the inability to taste food—captured by the expression "nothing is sweet in my mouth"—transcended ethnic and religious distinctions and united the Guinean immigrant community by providing a common way of reconciling memories of their war-torn homeland and their ongoing struggle for belonging in Europe.